2021
DOI: 10.2106/jbjs.20.01678
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Primary Total Knee Arthroplasty Following Septic Arthritis of the Native Knee

Abstract: Background: Septic arthritis of the native knee often results in irreversible joint damage leading to the need for total knee arthroplasty (TKA). The purpose of the present study was to examine the intermediate-term risk of periprosthetic joint infection (PJI), aseptic revision, and reoperation following primary TKA in patients with a history of septic arthritis of the native knee as compared with primary TKA performed for the treatment of osteoarthritis. Methods:We retrospectively identified 215 primary TKAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…The expert panel of the 2019 International Consensus on Orthopedic Infections emphasized the heterogeneity of SA-arthroplasty intervals, joint or bone involvements, the sites, and microorganisms in the publications available, which limited their conclusions and left them open to debate (Aalirezaie et al, 2019). Moreover, a recent case-control study involving 215 primary TKA (Bettencourt et al, 2021) revealed a 6.1-fold increased risk of PJI in patients undergoing TKA with a history of native knee SA when compared with controls undergoing TKA for osteoarthritis, with a cumulative incidence of 9 % at 10 years. Bettencourt et al (2022) did the same case-control study on the hip and found a 10-fold increased risk of PJI in patients with a history of SA.…”
Section: Discussionmentioning
confidence: 99%
“…The expert panel of the 2019 International Consensus on Orthopedic Infections emphasized the heterogeneity of SA-arthroplasty intervals, joint or bone involvements, the sites, and microorganisms in the publications available, which limited their conclusions and left them open to debate (Aalirezaie et al, 2019). Moreover, a recent case-control study involving 215 primary TKA (Bettencourt et al, 2021) revealed a 6.1-fold increased risk of PJI in patients undergoing TKA with a history of native knee SA when compared with controls undergoing TKA for osteoarthritis, with a cumulative incidence of 9 % at 10 years. Bettencourt et al (2022) did the same case-control study on the hip and found a 10-fold increased risk of PJI in patients with a history of SA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are significant, as patients who undergo arthroplasty following septic arthritis have been shown to have strikingly poorer outcomes than those undergoing arthroplasty for osteoarthritis. 21 …”
Section: Discussionmentioning
confidence: 99%
“…[16,19] Additionally, secondary osteoarthritis has several complications after total arthroplasty compared with primary osteoarthritis. [16,20] Therefore, prevention of secondary osteoarthritis is needed to improve patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[16][17][18] Secondary osteoarthritis is a serious problem that leads to pain, limping gait, and additional surgery, which comprises total arthroplasty and osteotomy. [16,19] Additionally, secondary osteoarthritis has several complications after total arthroplasty compared with primary osteoarthritis. [16,20] Therefore, prevention of secondary osteoarthritis is needed to improve patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%